The Influence of Financial Capability on MSME Performance: The Mediating Role of Digital Marketing and FinTech - Rosalia Cahya Arian; Amirul Arif (Journal of Educational Management Research, 2026)
This study aims to examine the effect of financial capability on MSME performance, both directly and indirectly through digital marketing and financial technology as mediating variables. A quantitative research approach was employed using questionnaire data collected from MSME actors. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the relationships among variables. The findings reveal that financial capability does not significantly affect MSME performance directly. However, financial capability has a significant positive effect on digital marketing and financial technology adoption. In addition, digital marketing and financial technology significantly improve MSME performance. The results further indicate that digital marketing and financial technology mediate the relationship between financial capability and MSME performance. These findings imply that strengthening MSME performance requires not only financial capability enhancement but also greater optimization of digital marketing strategies and financial technology utilization. The study contributes to the growing literature on MSME development by highlighting the strategic role of digital transformation in improving business performance.